Parthians in the Oxus Valley. Struggle for the Great Indian Road - Rtveladze, Eduard V. (Anabasis. Studia Classica et Orientalia, 2011)
The paper deals with the Parthian conquests in the East, including the eastern borders of the Parthian state. The author provides a range of evidence in favor of the idea that the middle Amu Darya (Oxus) River formed the eastern boundary of Parthia. It is possible, therefore, that for a period of time the Oxus valley as far east as the site of Kampyrtepa was in Parthian hands. According to the numismatic evidence, a section of the Amu Darya valley extending from Kampyrtepa to Kerki demarcated a portion of the Kushan state during Kanishka’s reign (i.e., the first half of the 2nd century AD).